Chemical composition and nutritive value of squilla (Oratosquilla nepa)- meal for White Leghorn layers - REDDY, V RAVINDER; REDDY, V RAMASUBBA; QUDRATULLAH, S (The Indian Journal of Animal Sciences, 2014)
The nutrient profile and feasibility studies of squilla-meal (SM) were conducted in 2 experiments with triplicate groups of WL layers, replacing fish mixture (FM), retaining the diets isocaloric and isonitrogenous. In experiment 1, SM was included at 0, 4.45, 8.89 and 13.34% and was fed from 210-315 days of age. In experiment 2, raw and autoclaved(1.09 kg/cm/2 for 15 min) SM replaced 13.34% of FM. Supplementation (0.05% and 0.1 %) of proteolytic enzymes was tested on raw SM diet from 175-280 days of age. The SM contained 3.39% CP, 1.86% EE, 7.28% Ca, 1.72% P and 1704 kcal of AME/kg. In experiment 1, hen-day egg production on 8.89% was comparable with that on control (74.8% vs. 78.7%) and at 13.34% level, it was significantly (P<0.01) lower (72.8%). Feed consumption was unaffected, while the feed etflciency at high levels ofSM (8.89% and 13.34%) was lower (1.82, 1.86) than control (1.69). Egg quality parameters did not show any specific trend. In experiment 2, proteolytic enzyme at 0.05% level to 13.34% SM diet improved the hen" day egg production and feed efficiency (92.6%; 1.53) in comparison to its unsupplemented diet (88.8%; 1.62) and comparable to that on control (93.1 %; 1.51). Autoclaving of SM was ineffecive. It is concluded that SM can be included up to 8.89% in layer diets without affecting egg production. Proteolytic enzyme at 0.05% is beneficial for complete replacement of fish-meal.